2005
DOI: 10.1016/s0840-4704(10)60298-0
|View full text |Cite
|
Sign up to set email alerts
|

Nursing and Patient Outcomes: It's Time for Healthcare Leadership to Respond

Abstract: An increasing body of research confirms the link between nursing variables (e.g. staffing ratios, skill mix) and patient outcomes including morbidity and mortality. This article presents the key themes that have emerged in this research and translates them into action for senior healthcare leaders. Immediate action is required in order for hospitals to effectively recruit and retain nurses, and to provide high quality patient care that minimizes risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…491 Other markers or proxy measures of leadership are associated with mortality. For example, a significant and positive association has been found between a higher percentage of clinicians on boards, the quality ratings of service providers and lower morbidity rates; 32 Mortality rates have also been linked to greater use of high-performance human resource practices; 492 nursing staffing ratios and skill mix 78, 493 and hospital pay for performance. 494 Wright et al 495 also found that good leadership, organisational management practices and information systems, supported by a quality improvement strategy based on robust local evidence, training and a community-wide approach, may be effective in reducing hospital mortality.…”
Section: Mortality Reviewsmentioning
confidence: 99%
“…491 Other markers or proxy measures of leadership are associated with mortality. For example, a significant and positive association has been found between a higher percentage of clinicians on boards, the quality ratings of service providers and lower morbidity rates; 32 Mortality rates have also been linked to greater use of high-performance human resource practices; 492 nursing staffing ratios and skill mix 78, 493 and hospital pay for performance. 494 Wright et al 495 also found that good leadership, organisational management practices and information systems, supported by a quality improvement strategy based on robust local evidence, training and a community-wide approach, may be effective in reducing hospital mortality.…”
Section: Mortality Reviewsmentioning
confidence: 99%